2019
DOI: 10.24215/25456377e079
|View full text |Cite
|
Sign up to set email alerts
|

Entre La Pedrera y Araracuara: la arqueología del medio río Caquetá

Abstract: La arqueología del medio río Caquetá, en la Amazonía colombiana, se conoció recién en los 1970s a partir de los resultados de proyectos de investigación pioneros en Araracuara y La Pedrera. Estas investigaciones identificaron secuencias cerámicas diferentes en cada localidad, documentaron una gran cantidad de petroglifos y, por primera vez, registraron suelos antrópicos negros y pardos en el Noroeste Amazónico. Investigaciones posteriores enfatizaron el estudio de archivos ambientales (arqueobotánicos y geoarq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…As for Zucchi [59], the Nofurei phase could represent innovations in the Camani phase due to contact with potters producing Japurá ceramics. For Arroyo-Kalin et al [72], the Nofurei phase shows important differences regarding other neighbouring and contemporaneous Amazonian Polychrome ceramics, such as the Napo, Tefé and Guarita phases, especially in the forms of vessels and modes of plastic and paint decoration, suggesting that such differences could be the result of a ceramics that derive from Pocó-Açutuba but is strongly influenced (in stylistic terms) by the expansion of groups in the Polychrome tradition and that the expansion of these latter groups could have pushed the original producers of Pocó-Açutuba ceramics towards the Araracuara and Peña Roja areas. Gomes & Neves [53] suggest that the arrival of the Polychrome tradition occurred in a friendly disposition with original producers of Pocó-Açutuba ceramics in the Japurá area, with relations such as intermarriage, commerce, imitation and emulation of ceramics between producers of both traditions in this section of the Amazon river.…”
Section: Japurá-caquetámentioning
confidence: 99%
See 4 more Smart Citations
“…As for Zucchi [59], the Nofurei phase could represent innovations in the Camani phase due to contact with potters producing Japurá ceramics. For Arroyo-Kalin et al [72], the Nofurei phase shows important differences regarding other neighbouring and contemporaneous Amazonian Polychrome ceramics, such as the Napo, Tefé and Guarita phases, especially in the forms of vessels and modes of plastic and paint decoration, suggesting that such differences could be the result of a ceramics that derive from Pocó-Açutuba but is strongly influenced (in stylistic terms) by the expansion of groups in the Polychrome tradition and that the expansion of these latter groups could have pushed the original producers of Pocó-Açutuba ceramics towards the Araracuara and Peña Roja areas. Gomes & Neves [53] suggest that the arrival of the Polychrome tradition occurred in a friendly disposition with original producers of Pocó-Açutuba ceramics in the Japurá area, with relations such as intermarriage, commerce, imitation and emulation of ceramics between producers of both traditions in this section of the Amazon river.…”
Section: Japurá-caquetámentioning
confidence: 99%
“…Unfortunately, for both scenarios we still need more solid evidence from the internal classification of JC-Arawakan languages 10 The migration of the Achagua-Piapoco was well summarized from an ethnological point of view by Vidal [30], who analysed the mythical narratives of the Piapoco and indicated that the ancestors of these groups left the Içana, went up the Vaupés from where they crossed to the upper Guaviare and from there to the Alto Orinoco and the Llanos Orientales. This path can also be represented in the archaeological record, such as the population growth in the Upper Orinoco with the arrival of the Piapoco and the archaeological sites of Granada and Manacacias [59,72], which corresponds to the routes mentioned in the mythical history of the Piapoco. Similar to Nofurei, Granada was classified as part of the Amazon Polychrome tradition, royalsocietypublishing.org/journal/rsfs Interface Focus 13: 20220050 which, according to Mora (1989: 192 fn 6) is supported by its chronology and its decorative style (white, red and black painting with complex geometric designs).…”
Section: Data Accessibilitymentioning
confidence: 99%
See 3 more Smart Citations